#ZimbabweanLivesMatter vs #ThisFlag: A comparative discourse analysis of two social media movements in Zimbabwe - Hundermark, Charné Lee (Centre for Film and Media Studies, 2023)
Zimbabwe's socio-political environment is characterized by political instability, rampant corruption and a general constitutional decay, in which oppressed citizens are restricted in their efforts to make their dissatisfaction heard (Sabao & Chikara, 2020). Under Robert Gabriel Mugabe's rule, citizen protest was often met with physical violence and intimidation tactics by the ruling party, a trend which has only continued under President Emmerson Dambudzo Mnangagwa's administration. Thus, a hesitancy to publicly protest has developed and continued, one that has only been exacerbated by the global COVID-19 pandemic. However, with the emergence of information and communications technology and the popularity of virtual networks such as Twitter, new forms of protest have emerged, forms centralised on interactive discourse. This study seeks to unpack this research problem by investigating two social media movements prolific under each administration, namely, #ThisFlag under the Mugabe administration and #ZimbabweanLivesMatter under the Mnangagwa administration. By presenting a comparative discourse analysis of the two campaigns, this study investigates the differences and similarities associated with campaign discourse, exploring the degree of continuity present across the two movements. Rather than examine the role social media played in each respective campaign, analysis of discourse provides an in-road to the key opinions, debates and concerns characteristic of the movements themselves. Notwithstanding this comparison, this study justifies that the success of digital activism is that it transcends geo-political borders and institutional constraints enforced by government, particularly as such constraints have continued despite the change in national leadership.